The relationship between learning experiences of the sub-topics of the benefits and efforts to preserve biodiversity towards environmental literacy - Rohmah, Annisa Nugrahaini Nur; Palupi, Della; Putri, Gustina Ika (Caraka Olah Pikir Edukatif, 2026)
Learning experiences are a series of activities designed to facilitate students in acquiring new knowledge and skills. Learning experiences have a strategic role in fostering environmental literacy. The purpose of this study was to determine the learning experience of the sub-material Benefits and Efforts to Preserve Biodiversity, to determine the results of environmental literacy level measurements, and the relationship between the two in phase E students of SMAN 1 Turi. This type of research is descriptive using the expository method with a correlational design. The data analysis approach used is quantitative descriptive. The average results of the learning experience of the sub-material, Benefits and Efforts to Preserve Biodiversity, tend to be in the moderate category of 39 or 73.58% of students. The average results of environmental literacy of phase E students are in the moderate category, of 53 or 100% of students. From the results of the simple linear regression test, the Sig. value is 0.000 < 0.005 and the Pearson Correlation value is 0.60 < 0.625 < 0.799. In conclusion, there is a positive and significant relationship between the learning experience of the sub-material Benefits and Efforts to Preserve Biodiversity and the environmental literacy of phase E students of SMAN 1 Turi, where both have a strong level of relationship.